Effect of Coupon Rate, Maturity Duration, and Rating on Sukuk Price Fluctuation: (Case Study at PT. Kustodian Sentral Efek Indonesia) - Chairul Akmal (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
The purpose of this study was to determine the effect of bond characteristics including coupon rate, maturity duration, and rating on fluctuations in the price of Sukuk in Indonesia, including Ijarah and Mudharabah Sukuk. The research method uses descriptive quantitative research with multiple regression analysis research model approaches. The results showed that the influence of bond characteristics, including coupon rate, maturity duration, and rating, on fluctuations in the price of corporate Sukuk in Indonesia was significant. Partially, which has a significant influence on fluctuations in the price of corporate Sukuk in Indonesia is the rating variable.